104 / 5.000 Performance Analysis of the Electricity Production System of the Karang Asam Diesel Power Plant in Samarinda, East Kalimantan, for the 2024 Operational Year - Alam Yurilianto Tulak; Fatkhul Hani Rumawan; Happy Nugroho; Muslimin Muslimin (ELECTROPS : Jurnal Ilmiah Teknik Elektro, 2025)
East Kalimantan faces a growing electricity demand of 12% annually, while production increases only by 8.5%, posing a potential energy crisis. Diesel Power Plants (PLTD) remain the primary solution, despite their reliance on depleting fossil fuels. This study evaluates the performance of PLTD Karang Asam throughout 2024 using efficiency and reliability indicators.The analysis reveals that the average Capacity Factor (CF) is only 2.04%, significantly below PLN’s standard of 55–65%. The Output Factor (OF) is recorded at 7.25%, indicating low utilization of output energy relative to installed capacity. The Load Factor (LF) stands at 2.82%, fluctuating between 0.26% and 10.83%, reflecting low capacity usage and operational instability. In terms of reliability, the Operating Availability Factor (OAF) reaches 85.99%, showing good operational readiness. However, disruptions persist, with an Outage Factor (OF) of 6.96% and an Outage Rate (OR) of 1.1. Fuel consumption efficiency remains within PLN’s standard, with an average Specific Fuel Consumption (SFC) of 0.283. To improve efficiency and ensure sustainable electricity supply, PT PLN plans to implement a dieselization program, replacing PLTD with power plants based on New and Renewable Energy (NRE). This transition aims to reduce dependence on fossil fuels and enhance the stability of East Kalimantan’s power system.